Operationalizing Heedful Interrelating: How Attending, Responding, and Feeling Comprise Coordinating and Predict Performance in Self-Managing Teams - Stephens, John Paul; Lyddy, Christopher J. (Frontiers in Psychology, 2016)
Team coordination implies a system of individual behavioral contributions occurring within a network of interpersonal relationships to achieve a collective goal. Current research on coordination has emphasized its relational aspects, but has not adequately accounted for how team members also simultaneously manage individual behavioral contributions and represent the whole system of the team’s work. In the current study, we develop theory and test how individuals manage all three aspects of coordinating through the three facets described in the theory of heedful interrelating. We operationalize the facet of contributing as distributing attention between self and others, subordinating as responsively communicating, and representing as feeling the system of the team’s work as a cohesive whole. We then test the relationships among these facets and their influence on team performance in an experiment with 50 ad hoc triads of undergraduate student self-managing teams tasked with collectively composing a song in the lab. In analyzing thin-slices of video data of these teams’ coordination, we found that teams with members displaying greater dispersion of attentional distribution and more responsive communicating experienced a stronger feeling of the team as a whole. Responsive communication also predicted team performance. Accounting for how the three aspects of coordinating are managed by individual team members provides a more critical understanding of heedful interrelating, and insight into emergent coordination processes.